2014
DOI: 10.1177/1362168814541715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of visual support on the processing of multiclausal sentences

Abstract: Processing morphemic elements is one of the most difficult parts of second language acquisition (DeKeyser, 2005;Larsen-Freeman, 2010). This difficulty gains prominence when second language (L2) learners must perform under time pressure, and difficulties arise in using grammatical knowledge. To solve the problem, the current study used the tenets of multimedia learning theory (Mayer, 2005) to help L2 learners' reconstruct multiclausal sentences. This theory assumes that limitations in cognitive capacity are red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Such observations inspire L2 Japanese researchers to determine the degree of difficulty of the acquisition of specific morpho-syntactic features of Japanese in relation to learners’ L1 backgrounds, highlighting structural differences between Japanese and other languages (e.g., Takemura, 2011; Nakamata, 2013; Cheng, 2015; Nagai, 2015; Anubhuti, 2018). Another category of studies address a range of issues discussed in SLA research including acquisition paths (e.g., Grüter, Lieberman, & Gualmini, 2010; Kawaguchi & Di Biase, 2012; Yabuki-Soh, 2012; Iwasaki & Oliver, 2014; Matsumoto & Nakayama, 2014), instruction and corrective feedback (Nakaue, 2012; Usami, 2013; Sugo, 2014; Hagiwara, 2015), and L2 syntactic attrition as an emerging area of interest (e.g., Russell, 2012).…”
Section: Cognitive Dimensions Of L2 Japanese Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Such observations inspire L2 Japanese researchers to determine the degree of difficulty of the acquisition of specific morpho-syntactic features of Japanese in relation to learners’ L1 backgrounds, highlighting structural differences between Japanese and other languages (e.g., Takemura, 2011; Nakamata, 2013; Cheng, 2015; Nagai, 2015; Anubhuti, 2018). Another category of studies address a range of issues discussed in SLA research including acquisition paths (e.g., Grüter, Lieberman, & Gualmini, 2010; Kawaguchi & Di Biase, 2012; Yabuki-Soh, 2012; Iwasaki & Oliver, 2014; Matsumoto & Nakayama, 2014), instruction and corrective feedback (Nakaue, 2012; Usami, 2013; Sugo, 2014; Hagiwara, 2015), and L2 syntactic attrition as an emerging area of interest (e.g., Russell, 2012).…”
Section: Cognitive Dimensions Of L2 Japanese Developmentmentioning
confidence: 99%
“…As far as instructional support for L2 Japanese syntactic development is concerned, support in accordance with learners’ cognitive processing capacities might be most effective. Hagiwara (2015), for example, demonstrated that JFL students processed aurally presented morphemic elements in multiclausal sentences significantly better with pictorial information than without visual support, as measured by accuracy in sentence repetition. The effect of pictorial support, however, was found only for newly learned elements or those in the sentence-final position.…”
Section: Cognitive Dimensions Of L2 Japanese Developmentmentioning
confidence: 99%
“…Although the majority of studies have demonstrated the advantages of multimodal input (e.g., Chen et al, 2012 ; Hagiwara, 2015 ; Peters, 2019 ), some researchers have reported that multimodal input did not lead to more efficacious L2 lexicon acquisition, and even had an adverse impact on L2 vocabulary acquisition (e.g., Lwo and Lin, 2012 ; Liu et al, 2018 ; Warren et al, 2018 ), which was theoretically consistent with CLT (Sweller, 2005 ). CLT posits that the amount of information that can be processed at one time in working memory is limited.…”
Section: Introductionmentioning
confidence: 99%